Sintesis Surfaktan Metil Ester Sulfonat Dari Palm Oil Methyl Ester Dan Natrium Metabisulfit Dengan Penambahan Katalis Kalsium Oksida - Harti, Jatikta Yuni; Nirwana, Nirwana; Irdoni, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Surfactants (surface active agent) is a chemical compound used for reduce the surface tension of the liquid. Surfactants are divided into four groups: anionic, nonionic, cationic and amphoteric. The most widely used surfactant is an anionic surfactant which is synthesized from petroleum namely Linear Alkylbenzene sulphonate (LABS). LABS is not resistant to high salinity levels, not degradable, expensive and still imported. Methyl Ester Sulfonate is an anionic surfactant which is currently being developed. These surfactants can be produced from palm oil methyl ester. MES produced from sulfonation reaction with addition of sulfonate. Sulfonate used in this research using sodium metabisulphite. The aims synthesize surfactant Methyl Ester Sulfonate of Palm Oil Methyl Ester usingSodium Metabisulphite and a catalyst Calcium Oxide, and to study the effects of time and the mole ratio of the product produced. Palm Oil Methyl Ester obtained from PT. Cemerlang Eka Perkasa Dumai, Riau Province. Sulfonation process carried out at the time variation of 4, 5, 6 hours, the mole ratio of 1: 0,5, 1:1, 1: 1,5, temperature of 80Â° C and the stirring speed of 450 rpm. The density of MES (0.89490 g/cm3 - 0.89545 g/cm3), viscosity (2.0323 cP - 2.1329 cP), a pH (2,03 - 2,48), surface tension (32.60 mN/m - 33.60 mN/m), interfacial tension (30.45 mN/m - 30.94 mN/m), and the stability emulsion (59.17% - 89, 17%).Keywords: methyl ester, methyl ester sulfonate, sulfonated, surfactant